The deflocculation of kaolin suspensions : the effect of various electrolytes - Penkavová, V. (2013)
The deflocculation effect of conventional additives to kaolin suspensions is evaluated from the results standard rheological measurements. Several widely used electrolytes (NaOH, Na2C03, Na2Si03, SHMP = sodium hexametaphosphate, and CMC = sodium salts of carboxymethylcellulose) have been tested. The optimal concentrations of these deffloculants, in respect to reaching the maximum reduction of initial suspension viscosity, are found. The stability of deflocculated kaolin suspensions against sedimentation is evaluated and different aspects of the observed flow enhancement discussed. Inorganic electrolytes are found to be more effective in viscosity reduction, but on the other hand, low-molecular organic CMC additives produce more stable final suspensions.